Pengaruh Kompetensi Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Pt.Tokai Texprint Indonesia - Uwais Rachman Karomi; Nelly Martini (Journal of Economic, Bussines and Accounting (COSTING), 2021)
This study aims to determine the effect of competence and work motivation on employee performance at PT. Tokai Texprint Indonesia. The method used is descriptive verification with quantitative methods, data collection techniques using simple random sampling. The number of samples in this study amounted to 170 respondents. The data analysis technique used is Path Analysis. The results of hypothesis testing are known to Sig. F < (0.000 < 0.05) indicates that there is a simultaneous significant effect of the variables of Competence and Work Motivation on Employee Performance. In addition, it can also be seen that Sig. t < (0.000 < 0.05) indicates that there is a partially significant effect of the variables of Competence and Work Motivation on Employee Performance. The R Square value is 0.840 or 84.0%. This means that the Competence and Work Motivation variables contribute to the Employee Performance variable by 84.0%. While the remaining 16% of Employee Performance variables will be influenced by other variables that are not discussed in this study. Keywords: Competence, Work Motivation, Employee Performance